Pengaruh Financial Distress, Ukuran Perusahaan Terhadap Manajemen Laba: Studi Kasus pada Perusahaan yang Terdaftar di Jakarta Islamic Index 30 Periode 2020-2022 - Wahyu Hidayat; Evan Hamzah Muchtar; Lala Amelia (Economic Reviews Journal, 2025)
Financial Distress is a situation where the cash in a company cannot fulfill its obligations so that a company is required to take action. This research is to find out how much influence financial distress and company size have on earnings management. This research uses independent variables, namely Financial Distress, Company Size and the dependent variable Profit Management. The population in this research is the 2020-2022 research period and the sample size is the 30 most liquid sharia shares listed on the Jakarta Islamic Index. The type of research in this research is quantitative descriptive research. The analysis used in this research is descriptive statistics, panel data regression, Chow test, Hausman test, hypothesis test, t test, f test, and coefficient of determination. This research will use the Eviews 12 programprogram to process data. The research results show that there is a positive influence of financial distress on earnings management. Meanwhile, the regression equation obtained a value of 0.263111 so that the analysis results show that the t-value is greater than t-table 1.66543 and P-value = 0.7932 > 0.05 so it can be concluded that company size has an effect on company performance. there is no influence on earnings management, and the calculated F value is greater than F table (-36.00000 > 1.99210), then it can be concluded that financial distress and company size simultaneously have a significant effect on earnings management.